Factors Affecting the Intention to Choose the Natural vaginal delivery based on the Theory of Planned Behavior among Primigravidae - Zakia Yaghobi; Hamidreza Mohaddes Hakkak; Hamid Tavakoli Ghoochani; Hamid Joveini; Mina Maheri; Masoumeh Taherpour; Seyed Hamid Hosseini (Hamadan University of Medical Sciences, 2019)
Aims: In the recent years, with regard to the uncontrolled growth of cesarean section (C-section) and the emphasis on increasing the indicator of Natural vaginal delivery (NVD) in Iran's Health System Transformation Plan, identifying the individual and social factors affecting this indicator have been necessary. Therefore, the aim of the present study was to determine the effective factors with the intention of choosing NVD based on the theory of planned behavior among primigravidae in Neyshabour city. Instruments & Methods: This cross-sectional study is descriptive-analytical research. It was done on 340 primigravidae with the age of 18-35 years old women referred to comprehensive urban health care centers of Neyshabour city, in 2018. Sampling was done by the multi-stage cluster sampling method. The information gathering tool included two parts. The first part of the study was demographic information and the second part was a researcher-made questionnaire based on direct and indirect constructs of the theory of planned behavior. Data were analyzed by SPSS 17 software using Kruskal-Wallis, Spearman correlation coefficient and multiple linear regression tests. Findings: 44.6% of the participants had the intention of performing C-section, 38.3% NVD, and 17.0% had no comment regarding the type of delivery intention. Four constructs; perceived behavioral control (β=0.224), attitude (β=0.199) and evaluation of behavioral outcomes (β=0.180), and normative beliefs (β=0.159) showed the highest positive and significant predictive value for NVD, respectively (p=0.001). The constructs of planned theory of behavior predicted 28.7% of the variance of NVD in pregnant women. Conclusion: The theory of planned behavior is suitable and useful for identifying the factors influencing the intention to perform NVD as well as designing and implementing educational interventions aimed at promoting NVD.